COOPERATION OPPORTUNITIES BETWEEN EURASIAN ECONOMIC UNION AND ASSOCIATION OF SOUTHEAST ASIAN NATIONS - A. Pakhomov; K. Bagdasaryan (Вестник университета)
The article examines modern economic and integration processes in the Association of Southeast Asian Nations (ASEAN) in the context of opportunities and constraints to implement the foreign economic policy of Russia and the Eurasian Economic Union (EAEU) in the region. The results of the research revealed systemic problems of an economic and administrative nature, those are limiting economic cooperation to projects of a narrow group of state corporations and state companies, mainly in the field of foreign trade, energy and military-technical cooperation. The analysis and conclusions can be used in the framework of bilateral consultations on cooperation of ASEAN and the EAEU. However, such cooperation has priority for Russia and EAEU and it should be viewed as a positive trend.